Контроллер руки робота на основе ИНС с применением моделирования MATLAB / SIMULINK - Павол, Божек; Владимир, Гога; Коршунов, Александр Иванович (Вестник ИжГТУ имени М.Т. Калашникова, 2013)
This paper describes the activity system and the importance of INS with the possibility of implementation to the robot control. The contribution also introduces the execution of DC motor regulation utilized for the positioning of a rotary positioned arm. The motor control comprises the current regulation, angular velocity and the rotation of the motor shaft fixed to the arm regarding the required angular change course of the arm rotation. The regulation structure of the DC motor is carried out in MATLAB/Simulink program. The arm movement is investigated via the mathematical model and virtual dynamic model formed in MSC.ADAMS program.